First-principles and machine-learning approaches for interpreting and predicting the properties of MXenes - José D. Gouveia; Tiago L. P. Galvão; Kais Iben Nassar; José R. B. Gomes (npj 2D Materials and Applications)
Abstract MXenes are a versatile family of 2D inorganic materials with applications in energy storage, shielding, sensing, and catalysis. This review highlights computational studies using density functional theory and machine-learning approaches to explore their structure (stacking, functionalization, doping), properties (electronic, mechanical, magnetic), and application potential. Key advances and challenges are critically examined, offering insights into applying computational research to transition these materials from the lab to practical use.